Measuring Supply Chain Performance through Migrant Workers Placement - Phong Thanh Nguyen; Quyen Le Hoang Thuy To Nguyen; Vy Dang Bich Huynh; Ngoc Bich Vu; Loan Phuc Le; Khoa Dang Vo; Phuong Thanh Phan; Andino Maseleno; Wahidah Hashim; Anggia Sari (International Journal of Supply Chain Management, 2019)
To facilitate existing procedures and improve decision making, a decision support system (SPK) needs to be built. This SPK aimed to determine the placement of workers abroad using the Simple Additive Weighting (SAW) method and supply chain process. This method was chosen because it is able to select the best alternative from a number of alternatives, in this case the alternative in question was someone who was entitled to receive Placement based on predetermined criteria. This research was conducted by looking for weight values for each individual. The Decision Support System produced was capable of ranking prospective Indonesian migrant workers and making it easier for BP3TKI to make decisions about Indonesian migrant workers by supply chain resource management for who will depart abroad.